Design and fabrication of vegetables washer / Muhammad Naqib Iqbal Mat Sehak - Mat Sehak, Muhammad Naqib Iqbal (2022)
Vegetables Washer can aid in the removal of dirt, germs, and pesticides from vegetables before they are cooked or consumed. However, this machine may take some time to remove all harmful substances from vegetables. The objective of this project is to help everybody wash vegetables without delivering any product damage. This project use the mechanical engineering design process method. Traditional cleaning can only clear away part of hazardous substances, which is far from a thorough cleaning and this machine can solve this problem as it can clean vegetables thoroughly. Furthermore, it also can be used to clean fruits.